Efficacy of imidacloprid/flumethrin collar in preventing canine leishmaniosis in Brazil - Alves, Graziella Borges [UNESP]; de Oliveira, Talita Carolina Bragança [UNESP]; Rodas, Lilian Colebrusco; Rozza, Daniela Bernadete [UNESP]; Nakamura, Alex Akira [UNESP]; Ferrari, Elis Domingos [UNESP]; da Silva, Debóra Regina Romualdo [UNESP]; Santos, Gisele Moraes dos [UNESP]; Calemes, Eliana Bravo [UNESP]; Requena, Keuryn Alessandra Mira Luz [UNESP]; Nagata, Walter Bertequini [UNESP]; Santos-Doni, Thais Rabelo; et al. (Hindawi, 2022)
The Leishmania infantum (synonym, Leishmania chagasi) causes life-threatening infection, namely canine leishmaniosis (CanL), which is a chronic zoonosis prevalent in various countries and spread by the bite of the infected Lutzomyia female sandfly in South America. The objective of the study was to assess the effectiveness of a polymer matrix collar containing made up of 10% imidacloprid and 4.5% flumethrin for the prevention of canine leishmaniosis from the hyperendemic region falling under Araçatuba municipality (Brazil). The research included a total of 146 dogs chosen from 75 households. Test were initiated via physical examination; weighing and biological sample collection (blood, popliteal lymph node and conjunctival swab) of these dogs were done in March 2018 (Day 0; GA, control = 69, GB, treated = 77) to initiate laboratory tests. Post-inclusion, the animals were monitored on the 120th, 240th, 360th and 480th days, respectively. The usage of collars continued between 0 and 480 days before being substituted in second (D240) and fourth (D480) follow-up visits. On the whole, 25 dogs in GA (36.2%) and three in GB (3.9%) were found positive for L. infantum infection in a minimum of one diagnostic test used in the research. Therefore, the average collar effectiveness for protection from L. infantum infection was 89.2% (p <.01). In the last follow-up, the average incidence density rate for GA was 30.7%, whereas for GB, it was 2.9%. The imidacloprid/flumethrin collars evaluated in the research were found to be safe and extremely efficient for the prevention of L. infantum infection through Lutzomyia species among the large population of dogs in highly prone endemic regions. This is a dependable and efficient technique aimed at reducing the occurrence and propagation of this illness among the population of canines, which would eventually reduce the human-health-related hazards. In Brazil, Lutzomyia spp. is a leading vector of the infection; thus, the collar can be used to limit infection in dogs and humans.
Keywords: canine leishmaniosis; dog; flumethrin; Leishmania; prevention; pyrethroids